1983
DOI: 10.1128/mcb.3.11.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of porcine major histocompatibility DNA sequences introduced into mouse L cells.

Abstract: The expression of a porcine genomic DNA segment containing a major histocompatibility gene and its chromatin structure in mouse L cells have been investigated. The transformed cells, which contain about two copies of the 17.8-kilobase pig DNA insert per haploid genome, stably and uniformly express major histocompatibility antigen on their surfaces. This expression is the result of differential transcription of the 3-kilobase major histocompatibility gene; the other 14 kilobases of pig sequences flanking the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This active negative regulation allows for rapid increases in transcription in response to immunomodulators or various conditions of stress. Indeed, numerous examples exist in which MHC class I expression increases in response to these situations, including treatment with interferons, tumor necrosis factor, or alcohol (23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…This active negative regulation allows for rapid increases in transcription in response to immunomodulators or various conditions of stress. Indeed, numerous examples exist in which MHC class I expression increases in response to these situations, including treatment with interferons, tumor necrosis factor, or alcohol (23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…One reason for the lack of lysis could have been the lower level of expression of the hybrid molecules by the L cell transfectants (Table II). To address this possibility, L cell transfectants were cultured for 24 h with IFN-3,, which increases MHC expression in transfected L cells (20). However, even under conditions in which the levels of expression of hybrid H-2 were almost equivalent (>90% of control) to the L cells transfected with the native molecule, no lysis was detected by serological analysis (Table III).…”
Section: Examination Of Polymorphic Determinants Using Ctl Derived Acmentioning
confidence: 99%
“…It has been indicated that IFNs increase MHC class I gene expression by acting on sequences within or in close proximity to the genes, since human and porcine MHC class I genes introduced into mouse cells increase their expression when treated with IFNs (25,27,39). Consistent with this assumption, Vogel et al (34) reported that promoter activity of a mouse class I gene is upregulated by IFNs via a 350-base-pair (bp) 5' flanking sequence.…”
mentioning
confidence: 99%